Khusyu’ as a Religious Coping Mechanism to Improve Psychological Well-being in Infertility and Involuntary Childlessness Couples - Nidaan Hasana; Muhammad Azhar; Tasman Hamami; Fitriah M. Suud (Jurnal Pendidikan Agama Islam, 2025)
Purpose – This study addresses the psychological distress faced by married Muslim couples who experience infertility and involuntary childlessness, particularly due to intense social and cultural pressures. It aims to explore how Khusyu’ (deep devotion in worship) functions as a religious coping mechanism to reduce stress, anxiety, and stigma associated with this condition Design/methods/approach – A qualitative phenomenological approach was used to capture the lived spiritual and psychological experiences of the participants. The study involved eight purposively selected Muslim couples from Magelang Regency, Indonesia, who had been married for more than three years without having children. Data were collected through in-depth interviews and observations, focusing on their religious practices and coping behaviors Findings – The results show that couples experiencing significant psychological distress engage in  Khusyu’practices, such as obligatory and additional prayers, supplication (du’a), voluntary fasting, and charity (sadaqah), as well as participation in Islamic study groups. These practices help reduce anxiety, foster acceptance of divine destiny, and build emotional resilience, while providing social support that mitigates stigma and strengthens marital harmony. Research implications/limitations – The implications of this study suggest that Khusyu’ as a form of religious coping can help childless couples manage psychological distress. Methodologically, the phenomenological approach enables an in-depth exploration of participants' spiritual and emotional experiences. However, given the qualitative nature of this study and the limited number of participants, the findings cannot be generalized to a broader population. Originality/value – This study provides a unique contribution by examining Khusyu’ as a specific religious coping strategy in the context of infertility among Muslim couples. Unlike previous research, which has focused broadly on religious coping, this study positions Khusyu’ as a central element in promoting psychological well-being and resilience within a distinct cultural and religious framework